Penerapan Klasifikasi Untuk Kelayakan Hasil Produksi Jam Tangan dengan Menggunakan Algoritma K-Nearest Neighbor - Maisevli Harika; Diena Rauda Ramdania; Rifaldo Sukma Hidayat; Safira Oktarini; Ferry Feirizal (STMIK Budi Darma, 2022)
Industrial companies in Indonesia are one of the sectors that require development in carrying out their contribution in the manufacturing world. Market needs become the main guideline for the industry to create new ideas and improve the quality of production. Most industries, including digital watch electronics companies, have a need to implement technology at every stage of manufacturing their goods, such as at the stage of filtering raw materials to checking quality control before the goods reach consumers. Filtering and quality control are carried out to maintain the quality of each product produced by the company. The problem discussed in this study is how to apply technology in detecting the quality of watch production using the K-Nearest Neighbor algorithm so that it can increase the quality of production, consumer confidence and increase profits for the company. The results of this study are that the model built using the K-Nearest Neighbor method can increase the accuracy for detecting quality control on watch products with an accuracy value of 92% for k = 3